Factors affecting consumers intention in purchasing eco-friendly cosmetic products in Batam City - Diarti, Yen; Hesniati, Hesniati (International Journal of Financial, Accounting, and Management, 2024)
Purpose: This study aims to identify the factors affecting consumer purchase intention towards ecologically sustainable cosmetic products in Batam City. The factors examined included subjective norms, promotion, perceived behavioral control, trust, and product quality. The data comprised of 322 questionnaires. The scope of this study was confined to Batam; therefore, the findings cannot be extrapolated to other areas.   Methodology: This study employed a survey to obtain data from consumers of cosmetic products in Batam. Results: The data analysis revealed that attitude, perceived behavioral control, sales promotion, product quality, and subjective standards significantly affected the intention to purchase green cosmetic products in Batam City. Nevertheless, trust does not have a significant effect on purchase intention. The findings of this study offer valuable insights for cosmetic companies to devise more efficient marketing strategies for green cosmetic products. Limitations: Data collection was exclusively conducted via questionnaires, which may have introduced respondent bias. Owing to its cross-sectional nature, this study could not elucidate temporal variations. A longitudinal study offers a more profound understanding of fluctuations in consumer intention over time. Contributions: This study validates consumer perspectives on green cosmetics and advocates for more explicit standards and regulations in the sector, and the use of sophisticated biotechnology to extract natural ingredients.